Women's Contribution to the Development of Woven Fabric Crafts in Pringgasela Tourism Village, East Lombok - Yuniati Yuniati; Salman Alam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Women play a central role in sustaining the woven textile craft industry, encompassing the production process, preservation of traditional motifs and natural dyes, as well as the development of woven fabric-based derivative products. This study aims to examine women's contributions to the development of woven textile crafts in Pringgasela Village, East Lombok. This research employs an exploratory qualitative approach, with data collected through Focus Group Discussions (FGD) and in depth interviews involving multiple stakeholders, including representatives of the East Lombok Regional Tourism Office, the Village Head of Pringgasela, the Chair of the Tourism Awareness Group (Pokdarwis), weavers, entrepreneurs, and community empowerment institutions. The findings reveal that women's contributions encompass: (1) the preservation of weaving traditions as a cultural attraction through dedicated weaving galleries; (2) institutional partnerships with Bank Indonesia through empowerment and capacity building programs; (3) active participation in the Alunan Budaya Festival as a medium of cultural education for younger generations; and (4) the utilization of digital platforms as a marketing channel for woven textile products. Nevertheless, the Pringgasela weaving industry continues to face several challenges, including limited market reach, insufficient regeneration of young artisans, and low adoption of digital technology among senior weavers. Holistic strengthening of empowerment strategies is therefore essential to ensuring the sustainability of the weaving industry alongside the preservation of local cultural heritage.